The Successful of Online Learning on Student Responsibility Characters During the COVID-19 Pandemic - Rahmat - Aziz; Muhammad Amin Nur; Raihan Retriansyah Dilapanga; Mega Arina Manasikan; Ulfiatul - Muarofah (Jurnal Pendidikan dan Pengajaran, 2022)
Learning activities to develop the character of responsibility during the COVID-19 pandemic have created difficulties for teachers as teaching guides and students as learning implementers. Teachers and students' problems appropriately and wisely help shape satisfying forms of responsibility character in education. This paper aims to explore student responsibility behavior in learning and analyze the roles of teachers during the learning process. This paper is based on data collected from open questionnaires to 58 students in senior high schools in Manado North Sulawesi, Pasirian East Java, and Malang East Java. Data collection through interviews with seven teachers and two school principals. The data were analyzed using descriptive analysis statistics and critical analysis techniques. The results showed that responsive and proportionate teachers in delivering learning have succeeded in developing responsible behaviors towards students. The selection of a suitable learning model and positive school support has become a determinant of success for the learning process of student responsibility. This paper suggests the need for a more in-depth data collection method to understand cases comprehensively.